2019
DOI: 10.1002/ceat.201900063
|View full text |Cite
|
Sign up to set email alerts
|

Mixing Time in Intermediate‐Sized Orbitally Shaken Reactors with Small Orbital Diameters

Abstract: Orbitally shaken reactors (OSR) are widely used in bioprocess development; however, a scaling law between large reactors, usually shaken in incubators at an orbital diameter of d o = 1.5-5 cm, and microwell plates, shaken in benchtop thermomixers at d o = 3 mm, is still missing. Here, the mixing time was measured in two reactors with the same volume but either cylindrical or square geometry for d o = 3 mm. For such a small d o , the acceleration mode to reach the final speed in the cylinder was found to greatl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 22 publications
(39 reference statements)
1
6
1
Order By: Relevance
“…It is evident that an increase in mixing time was resulted from a decrease in free surface height and vice versa. A similar phenomenon was also noticed in the work of Li et al [30] where a direct acceleration mode affected the free surface oscillations and thus the mixing time in an intermediate-sized cylindrical reactor when shaken in ThermoMixer. The reduced free surface oscillation in the square microwell is independent of acceleration modes, however, the longer mixing time at high speed range was also due to a significantly reduced free surface height.…”
Section: Mixing Time In 24-dsw Plate Formatsupporting
confidence: 82%
See 4 more Smart Citations
“…It is evident that an increase in mixing time was resulted from a decrease in free surface height and vice versa. A similar phenomenon was also noticed in the work of Li et al [30] where a direct acceleration mode affected the free surface oscillations and thus the mixing time in an intermediate-sized cylindrical reactor when shaken in ThermoMixer. The reduced free surface oscillation in the square microwell is independent of acceleration modes, however, the longer mixing time at high speed range was also due to a significantly reduced free surface height.…”
Section: Mixing Time In 24-dsw Plate Formatsupporting
confidence: 82%
“…300 -400 rpm), while no significant change in mixing time observed for shaken speeds greater than 400 rpm and the mixing process became very rapid afterwards. It should also be noticed that contrary to the work of Li et al [30], no difference in mixing time was identified in the cylindrical microwell when different acceleration modes was adopted.…”
Section: Comparison Of Mixing Time In Different Well Geometriescontrasting
confidence: 67%
See 3 more Smart Citations